2020
DOI: 10.1002/uog.22224
|View full text |Cite
|
Sign up to set email alerts
|

OC04.05: The interwoven effect of maternal age and co‐morbidities in COVID‐19 fatality among pregnant women: the Mexican national cohort

Abstract: Oral communication abstracts obstetrical ultrasound for patients in underserved rural and remote communities where this service is not available. The objective of this study is to assess the feasibility of providing obstetrical ultrasound services remotely using a telerobotic ultrasound system in a remote community isolated due to COVID-19. Methods: A telerobotic ultrasound system was used to remotely perform obstetrical ultrasound exams in La Loche, Canada, a remote community without regular access to obstetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The average age of respondents is 28.33+4.82 years with a tendency towards young adults (21-30 years). Different from the previous study by Martinez et al 9 which showed that advanced age with an increased risk of complications and maternal death. This may be influenced by the health protocols and contact tracing which comes from asymptomatic relatives or spouses.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The average age of respondents is 28.33+4.82 years with a tendency towards young adults (21-30 years). Different from the previous study by Martinez et al 9 which showed that advanced age with an increased risk of complications and maternal death. This may be influenced by the health protocols and contact tracing which comes from asymptomatic relatives or spouses.…”
Section: Discussioncontrasting
confidence: 72%
“…The majority of subjects had no comorbidities (73.5%), however Martinez et al 9 study showed that subjects with comorbidities were more common and associated with increased mortality. 9 The presence of comorbidities in a patient does not determine the risk for COVID-19, however it can increase the patient's poor outcome. Most of the pregnant women with COVID-19 had mild to moderate eJKI Vol.…”
Section: Discussionmentioning
confidence: 97%
“…(1) a CURB-65 score for pneumonia > 1 point; (2) persistent fever > 39 • C; (3) comorbidity such as chronic hypertension, chronic pulmonary obstructive syndrome, pregestational diabetes or treatment with immunosuppressant drugs; and (4) chest X-ray showing signs of pneumonia 16 . Asymptomatic patients and patients with negative RT-qPCR for SARS-CoV-2 were excluded, as they did not require hospital admission or additional biochemical evaluation according to our protocol.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The ACE2 receptor, which is upregulated during a typical pregnancy, is where SARS-CoV-2 enters human cells and binds. Additionally, increased expression of ACE2 receptors is linked to advancing age, which may contribute to the disease's worsening severity (Martinez Portilla et al, 2020).…”
Section: Discussionmentioning
confidence: 99%